2015
DOI: 10.1007/s11431-014-5751-6
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of grayscale values of cement constituents using industrial X-ray tomography

Abstract: X-ray computer tomography (CT) has been intensively applied to the research of cement-based materials, while most of the CT applications are qualitative. To have more quantitative applications, the arbitrary grayscale values and the specially defined CT numbers of the main cement constituents, including the cement clinkers, the hydrated products, and some durability products are calibrated on an industrial CT system in this study. The calibration results can deepen our understandings of the X-ray CT image of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast, the cracked sample contained three phases: (1) a gas phase including cracks and empty microcapsules; (2) a liquid phase of intact microcapsule core materials; (3) a solid phase including cement-bentonite matrix and the precipitated sodium silicate that was released from the microcapsules. However, the linear attenuation coefficients of the gas phase and liquid core phase are very close, both of which appear as black in the cracked sample, making it difficult to isolate one from the other (Wan et al, 2015;Ahmed, 2015;Lv et al, 2016). No major cracks can be observed around the shell of microcapsules in the undamaged specimen, indicating that the microcapsules survived the mixing process and no premature release of sodium silicate occurred.…”
Section: Micro-ct Imaging Analysismentioning
confidence: 99%
“…In contrast, the cracked sample contained three phases: (1) a gas phase including cracks and empty microcapsules; (2) a liquid phase of intact microcapsule core materials; (3) a solid phase including cement-bentonite matrix and the precipitated sodium silicate that was released from the microcapsules. However, the linear attenuation coefficients of the gas phase and liquid core phase are very close, both of which appear as black in the cracked sample, making it difficult to isolate one from the other (Wan et al, 2015;Ahmed, 2015;Lv et al, 2016). No major cracks can be observed around the shell of microcapsules in the undamaged specimen, indicating that the microcapsules survived the mixing process and no premature release of sodium silicate occurred.…”
Section: Micro-ct Imaging Analysismentioning
confidence: 99%
“…While the development of this technique has been mainly driven by its invaluable use in medical diagnostics [9], it is also a useful tool for nondestructive inspection of building materials [10,11]. In particular, it has been shown that the technique is suitable for identifying the different components of cement-based materials [12,13], and that the technique can be used to visualize the material changes associated with cement degradation through leaching [14]. In previous work, it was determined that X-ray computed tomography may indeed provide a detailed description of AC pipe degradation [15].…”
Section: Introductionmentioning
confidence: 99%
“…While the development of this technique has been mainly driven by its invaluable use in medical diagnostics, it is also a useful tool for the non-destructive inspection of building materials. In particular, it has been shown that the technique is suitable for identifying the different components of cement-based materials [3,4] and that the technique can be used to visualize the material changes associated with cement degradation through leaching [5]. CT should therefore prove to be a valuable tool to provide a more detailed view of AC pipe degradation.…”
Section: Introductionmentioning
confidence: 99%